2016
DOI: 10.1007/s12033-016-9959-5
|View full text |Cite
|
Sign up to set email alerts
|

G5, a Phage Single-Stranded DNA-Binding Protein, Fused with a Nuclear Localization Signal, Attenuates Symptoms and Reduces Begomovirus-Betasatellite Accumulation in Transgenic Plants

Abstract: Cotton leaf curl disease is caused by several monopartite begomoviruses and is the major threat to cotton production in the Indian subcontinent. The disease has been shown to be associated with four distinct species, including Cotton leaf curl Kokhran virus (CLCuKoV), and a specific betasatellite-Cotton leaf curl Multan betasatellite (CLCuMuB). Transgenic Nicotiana benthamiana plants were produced which constitutively express the Escherichia coli phage M13 encoded, sequence nonspecific single-stranded (ss) DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Our study showed that transgenic N. benthamiana lines expressing G5fused with the maize opaque-2 nuclear localization signal (NLS) have tolerance to ToLCNDV. This extends earlier work on G5, which showed this to provide tolerance to infection by a monopartite betasatellite-associated begomovirus (Rasool et al 2016), and indicates that G5 may be a useful tool in generating crops with broad spectrum resistance to begomoviruses.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Our study showed that transgenic N. benthamiana lines expressing G5fused with the maize opaque-2 nuclear localization signal (NLS) have tolerance to ToLCNDV. This extends earlier work on G5, which showed this to provide tolerance to infection by a monopartite betasatellite-associated begomovirus (Rasool et al 2016), and indicates that G5 may be a useful tool in generating crops with broad spectrum resistance to begomoviruses.…”
supporting
confidence: 82%
“…Overall, these results are in agreement with an earlier study, using the same transgenic NLS-G5 N. benthamiana lines, which showed resistance to the monopartite begomovirus cotton leaf The molecular detection show PCR and Southern hybridization detection results. Southern blots showed no hybridization (N) from non-symptomatic plants, low hybridization (L) resulted from mild symptomatic plants and high levels of hybridization (H) from severely symptomatic plant samples curl Kokhran virus (CLCuKoV) in the presence and absence of its cognate betasatellite (Rasool et al 2016). In the previous study, a significant proportion of inoculated plants did not develop symptoms as found in our work.…”
Section: R I P L I C a T E S U S I N G T H E T W O P R I M E R S E T mentioning
confidence: 99%
See 1 more Smart Citation
“…The coat protein (CP) sequence of CLCuKoV-Bu was assembled and compared with the (accession number HF549183) CPs of other begomoviruses in the database, using BLAST (Mullineaux et al, 1988). The detailed mechanism of point mutations introduced in the CP sequence has been mentioned in Rasool et al (2016a). The designed mutated CP construct was codon optimized for Gossypium hirsutum (http://www.…”
Section: Production Of Cp Syn Expression Cassettesmentioning
confidence: 99%